Influence of Music Therapy and Music-Based Interventions on Dementia: A Pilot Study. (5th May 2021) - Dahms, Rebecca; Eicher, Cornelia; Haesner, Marten; Mueller-Werdan, Ursula
Abstract: According to national dementia plan in many countries, the music implementation into the daily routine as an adjunctive therapy to medication treatment is common. However, the ability of long-term care facilities to implement individualized music therapy (MT) and music-based interventions is not sufficiently taken into account. This pilot study examined the frequency of use and acceptance of MT and technology-based music interventions (TBMI) as well as the influence of high and low usage of both interventions of dementia on behavioral and psychological symptoms (BPSD) at two timepoints. Furthermore, the influence on the combination of MT and TBMI of dementia within the nursing home setting on BPSD with a focus on agitation, apathy, depression, and quality of life at all timepoints was considered. In the present study, data from 30 people with dementia (PwD) aged on average 81 years were analyzed within an eight-week noncontrolled intervention study, including four-week follow-up. Initial outcome data indicated significant decreases at times T2 and T3 in agitation and apathy among PwD with a high usage of MT and TBMI than among those with a low usage. In general, reductions were obtained from all observed BPSD at all timepoints. Significant results were found only for agitation over time. Considering the demonstrated results, a long-term implementation of music within daily routines in nursing homes for PwD should be strived for.